Prevalence of Hepatitis in Prisoners: A Systematic Review of Current Evidence - Pashangzadeh, Salar; SeyedAlinaghi, SeyedAhmad; Dadras, Omid; Pashaei, Zahra; Soleymanzadeh, Mahdi; Barzegary, Alireza; Mirzapour, Pegah; Vahedi, Farzin; Fakhfouri, Amirata; Noori, Tayebeh; Hossein Irani, Seyed Mohammad; Mehraeen, Esmaeil; et al. (Infectious Disorders - Drug Targets, 2022)
Introduction: Prisoners represent high-risk behaviors such as injecting drug use, sharing syringes, tattooing, and unprotected sexual intercourse. The authors aimed to study the prevalence of hepatitis B, hepatitis C, and hepatitis D in the prisoners. Methods: We conducted a systematic search using the keywords in online databases of PubMed, Web of Science, Scopus, and Science Direct. Two independent researchers examined the quality of the articles and the probable risk of bias. The most relevant articles by title and abstract were retrieved. Finally, the full text of selected articles was read, and the critical findings were extracted. Results: Reviews of 23 studies showed that most prisoners are susceptible to hepatitis B and hepatitis C. One study also indicated that prisoners could be infected with hepatitis A and hepatitis E. The most common routes of hepatitis transmission in prisons were intravenous drug use, needle sharing, tattooing, and unsafe sex with multiple sexual partners. Conclusion: High-risk sexual behaviors, shared contaminated needles for IV drug injection, and tattooing are the principal routes of hepatitis transmission among prison inmates. Hepatitis treatment is feasible and could be useful for infected prisoners undergoing a well-designed treatment program.
Keywords: liver disease